Optimizing Socialization Management for Student Enrollment Growth: A Qualitative Study of Integrated Islamic Boarding School Marketing Strategies - Ridha Nurhaliza; Suhrawardi Suhrawardi; Amalia Irfani; Diena Juliana (Islam and Social Sciences Review, 2025)
This study aims to analyze socialization management in increasing new student enrollment in an integrated Islamic senior high school context. This research employs a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation involving key informants, including the school principal, the new student admission committee (PPDB), the vice principal for student affairs, and parents. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured using source and technique triangulation. The findings reveal that socialization management has been systematically implemented through the stages of planning, organizing, actuating, and controlling by utilizing both digital and conventional media. However, the increase in new student enrollment has not been fully optimal due to socioeconomic constraints and the characteristics of the boarding school system. This study is limited by its single case study design, which restricts the generalizability of the findings, yet it provides theoretical implications for the development of socialization management within the framework of Islamic education marketing. Practically, this study offers recommendations for educational institutions to develop adaptive, community-oriented socialization strategies and strengthen collaboration with external stakeholders to enhance institutional attractiveness. The originality of this study lies in integrating socialization management with value-based Islamic educational marketing in a boarding school context. Keywords: Socialization Management, Student Enrollment, Educational Marketing, Integrated Islamic School, Boarding School